Teaching Conceptual Modelling in Cultural Heritage - Gonzalez-Perez, Cesar; Martín-Rodilla, Patricia (Revista de Humanidades Digitales, 2017)
Specialists in the humanities and social sciences often construct models of the realities they work with; these models are usually expressed in natural language, as thesauri, or by similarly informal means. Conceptual modelling, a more formalised approach, has been used in other fields for some time, and we hypothesised that its usage in the cultural heritage field would allow specialists to create better and more powerful models. With this aim, in 2011 we launched an education program on conceptual modelling for cultural heritage. After five years and numerous experiences, we report here that specialists in cultural heritage with no previous exposure to modelling systematically learn the necessary techniques and show themselves able to develop rich models. Experience also shows that satisfaction about the approach is very high.